PENGARUH TINGKAT PENGANGGURAN TERBUKA (TPT) DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP KEMISKINAN PROVINSI SUMATERA UTARA - Karolinska, Karolinska; Panjaitan, Irawati; Simamora, Renny (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Poverty continues to be a major problem in the world, especially in Indonesia, which is a developing country. This study has the aim of testing and analyzing the Open Unemployment Rate (TPT) and the Human Development Index (HDI) to determine the number of poor populations in North Sumatra Province. This type of data uses secondary data obtained from the Central Statistics Agency (BPS). The secondary data used in this study is time series data in North Sumatra Province from 2008 to 2020. This study aims to determine whether the independent variables, in the form of the Open Unemployment Rate (TPT) and the Human Development Index (HDI), have a relationship that is interrelated with the dependent variable, namely the number of poor populations. The results of this study are as follows: (a). The Open Unemployment Rate (TPT) has a positive and significant effect on poverty in North Sumatra Province (b). The Human Development Index (HDI) has a negative and significant effect on poverty in North Sumatra Province.